Peningkatan Keterampilan Membentuk Relief Plastisin Menggunakan Model Pembelajaran Langsung di Sekolah Dasar - Harni Harni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was to improve skills in forming reliefs from plasticine material in elementary schools using the direct learning model. This research is a research conducted using quantitative and qualitative approaches. The subject of the research was the teacher and fourth grade students of elementary school in the city of Padang. The results showed that an increase in skills formed a relief in the form of: the RPP assessment had increased from 84.71% to 94.44%. From the teacher aspect there was an increase from 76.56% to 95.31%, and the student aspect had increased from 70.31% to 90.62%. In the assessment of student skills improvement occurs from an average value of 70.76, increasing to 85.98.